2019
DOI: 10.3390/polym11030487
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Radical Copolymerization Kinetics of 2-Hydroxyethyl Methacrylate and Butyl Methacrylate

Abstract: 2-Hydroxyethyl methacrylate (HEMA) is an important component of many acrylic resins used in coatings formulations, as the functionality ensures that the chains participate in the cross-linking reactions required to form the final product. Hence, the knowledge of their radical copolymerization kinetic coefficients is vital for both process and recipe improvements. The pulsed laser polymerization (PLP) technique is paired with size exclusion chromatography (SEC) and nuclear magnetic resonance (NMR) to provide ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 36 publications
(119 reference statements)
0
35
0
Order By: Relevance
“…Copolymer composition was determined from 1 H NMR analysis conducted with a Bruker 400 MHz spectrometer and DMSO‐d 6 as solvent. Peaks assignments for the ─O─CH 2 ─ protons for MEA [ 9 ] and the ─O─CH 2 ─ and ─OH signals for HEMA [ 19 ] in DMSO‐d 6 were taken from previous studies, with peak assignments indicated on the poly(MEA‐co‐HEMA) 1 H NMR spectrum shown in Figure S5 in the Appendix S1. Peaks arising from HEMA monomer were usually not observed in the NMR spectra after purification of the poly(MEA‐co‐HEMA) samples; however, when necessary, peak integrations were adjusted to account for its presence when determining FMEA according to Equations () and (): 0.25emFMEA=1italicOH4.80.25emitalicppm12()OCH23.80.25emitalicppm+OCH24.20.25emitalicppm 0.25emFMEA=1italicOH4.80.25emitalicppm12()italicOCH23.40.25emitalicppm+italicOCH23.70.25emitalicppm Equation () was used to determine FMEA in this study, as occasionally the OCnormalH23.40.25emppm signal overlapped with the H 2 O (or HOD) peak of DMSO‐d 6 appearing at 3.3 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Copolymer composition was determined from 1 H NMR analysis conducted with a Bruker 400 MHz spectrometer and DMSO‐d 6 as solvent. Peaks assignments for the ─O─CH 2 ─ protons for MEA [ 9 ] and the ─O─CH 2 ─ and ─OH signals for HEMA [ 19 ] in DMSO‐d 6 were taken from previous studies, with peak assignments indicated on the poly(MEA‐co‐HEMA) 1 H NMR spectrum shown in Figure S5 in the Appendix S1. Peaks arising from HEMA monomer were usually not observed in the NMR spectra after purification of the poly(MEA‐co‐HEMA) samples; however, when necessary, peak integrations were adjusted to account for its presence when determining FMEA according to Equations () and (): 0.25emFMEA=1italicOH4.80.25emitalicppm12()OCH23.80.25emitalicppm+OCH24.20.25emitalicppm 0.25emFMEA=1italicOH4.80.25emitalicppm12()italicOCH23.40.25emitalicppm+italicOCH23.70.25emitalicppm Equation () was used to determine FMEA in this study, as occasionally the OCnormalH23.40.25emppm signal overlapped with the H 2 O (or HOD) peak of DMSO‐d 6 appearing at 3.3 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…By selecting the appropriate solvent, it is possible to break the intermolecular hydrogen bonds which result in a decrease in HEMA reactivity or introduce competitive hydrogen bonds what results in increase in HEMA reactivity. 39 Choosing the right solvent for copolymerization of HEMA allows to control the distribution of units in the copolymer chain. 39,40 The impact of hydrogen bonds on the solubility of PHEMA in water was described by Weaver et al 36 The authors observed that at a degree of polymerization below 30, PHEMA was soluble in water at any temperature.…”
Section: Introductionmentioning
confidence: 99%
“…39 Choosing the right solvent for copolymerization of HEMA allows to control the distribution of units in the copolymer chain. 39,40 The impact of hydrogen bonds on the solubility of PHEMA in water was described by Weaver et al 36 The authors observed that at a degree of polymerization below 30, PHEMA was soluble in water at any temperature. For degrees of polymerization in the range of 30-45, PHEMA was thermoresponsive in water.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, acceptably accurate propagation rate coefficients have been reported for the monomers: styrene, methyl acrylate, butyl acrylate, ethyl acrylate, hydroxyethyl acrylate, methyl methacrylate, butyl methacrylate, glycidyl methacrylate, 2-hydroxyethyl methacrylate, vinyl acetate, vinylidene fluoride, hexafluoropropylene, and tetrafluorethylene [ 200 , 201 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ].…”
Section: Case Studies For Connection Of Computational Chemistry and Kinetic Modelingmentioning
confidence: 99%